Effects of cross-training using silat practice on psychological profiles of young tennis players - Abdul Rahim, L. M. R.; Shapie, M. N. M.; Abdullah, N. M.; Parnabas, V.; Mohd Nor, M. A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. Silat has been found to support the development of psychological aspects in enhancing the mental toughness of an athlete. In tennis performance, psychological skills are important and it is crucial to include in the training routines. Problem and aim. Psychological factor has been identified by coaches that may affect the performance of junior tennis players. Psychological attributes that can be developed through silat practice may assist young tennis players improve their psychological performance. Therefore, this study investigated the effects of silat practice as a cross-training program on the mental toughness of junior tennis players in Malaysia. Material and methods. Thirty (n=30) nationally ranked junior tennis players between the ages of 12 to 16 years old (18 males and 12 females, mean age 14.29 ± 1.65 years) were selected using purposive sampling method and were equally divided into experi- mental and control groups. Both groups were involved with the same training sessions every day for eight weeks. However, the experimental group performed a 30-minute silat practice prior to their normal training sessions. All participants completed a 42 items Psychological Profiles Inventory (PPI) Questionnaire one day before and after the intervention. Results. The experimental group (n=15) showed significant improvement after the intervention while the results of the paired t-test analysis indicated that all the psychological profiles except negative energy showed a significant difference between the experimen- tal (n=15) and the control (n=15) groups after the 8 weeks of the intervention program. Conclusions. The results in this study validate the positive effect of silat practice on the mental toughness of junior tennis players.